Selection of Appropriate Equipment for Designing Effective Vacuum System - Akram, H. M; Khan, M Zafarullah (Review of Information Engineering and Applications, 2015)
Vacuum systems are designed for a variety of research activities and industrial performs for different vacuum ranges depending upon the process prerequisite. It is very essential that these systems should be designed by selecting the vacuum equipment for proper vacuum generation, precise vacuum measurement and particular vacuum control for immense contribution to the process effectiveness, operational ease, working efficiency and quality product. In this paper effort has been made to clarify the physical concepts to use variety of vacuum pumps, gauges and valves to design different vacuum systems with diverse vacuum ranges for their up to mark effectiveness.